2005
DOI: 10.1177/0165551505050789
|View full text |Cite
|
Sign up to set email alerts
|

Changes in queries in Gnutella peer-to-peer networks

Abstract: Abstract.Peer-to-peer (P2P) networks have been drawing significant attention in the area of information management and sharing recently. Unlike the World Wide Web (WWW), every peer in a P2P network is both client and server. It hosts information for sharing and submits queries to search for information from all of the other peers at the same time. There are a large number of studies related to the information behavior of WWW search engines in the US and Europe. Several issues have been investigated in these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Analyzing Gnutella queries in December 2000 and January 2001, Sripanidkulchai [26] also observed that 17% of the queries contained non-ASCII characters. Similarly, Yang et al [32] observed that 0.59% of queries issued in July 2002 were not in English. They also observed that by September 2003, 20.85% of the queries were not in English.…”
Section: Query Success Ratementioning
confidence: 87%
See 2 more Smart Citations
“…Analyzing Gnutella queries in December 2000 and January 2001, Sripanidkulchai [26] also observed that 17% of the queries contained non-ASCII characters. Similarly, Yang et al [32] observed that 0.59% of queries issued in July 2002 were not in English. They also observed that by September 2003, 20.85% of the queries were not in English.…”
Section: Query Success Ratementioning
confidence: 87%
“…This compares well to the median number of five terms in filenames (Figure 1(a) [33] reported that the average Gnutella object name and query had 8.47 terms and 3.91 terms, respectively. Yang et al [32] reported a median of three and average of 3.74 query terms in July 2002 and a median of four and mean of 5.21 query terms by September 2003.…”
Section: Number Of Terms In Filenames and Queriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis on the AltaVista query logs also has been reported (Silverstein, Henzinger, Marais, & Moricz, 1999). Similar studies on peer-to-peer Gnutella network also have been conducted (Kwok & Yang, 2004;Yang & Kwok, 2005); however, most of these studies focused on English search queries only. The information needs and search behaviors of users of non-English search engines can be very different from those of English search engines because of the different nature (e.g., grammar) of these languages and also the different cultures of non-English users.…”
Section: Introductionmentioning
confidence: 95%
“…Yang and Kwok (2005), researched about the changes in the queries made by users on Gnutella (one instance of P2P network) in 2002 and 2003, by saving the data of these queries in a log file and analyzing it using a database management system. They found an increased number of nonEnglish queries, also a decrease on the number of repeat queries but still more than that for WWW search engines, partly because most users know what file they are looking for when they make a query.…”
Section: Gnutellamentioning
confidence: 99%